Knowledge, attitudes, beliefs, and barriers associated with the uptake of influenza vaccine among pregnant women - Ahmed Y. Mayet; Ghadeer K. Al-Shaikh; Hazem M. Al-Mandeel; Nada A. Alsaleh; Amani F. Hamad (Saudi Pharmaceutical Journal, 2017)
Objective: The purpose of the study was to assess the knowledge, attitudes, beliefs, and factors associated with the uptake of the influenza (flu) vaccination in women within Saudi Arabia during their pregnancy period. Methods: A cross-sectional prospective survey was conducted on 1085 pregnant women at the antenatal clinic over a period of 6 weeks with the provision of influenza vaccination. The questionnaire collected demographic and other data; it included 12 questions on their general knowledge and assessed their attitude toward influenza vaccination, and their awareness of vaccine risk and the potential benefits during pregnancy. The knowledge score obtained was then calculated and compared. Results: A total of 998 patients took part in the questionnaire with a response rate of 92%. There was poor awareness that the flu vaccine is safe to administer during pregnancy (130, 13.1%) and that all pregnant women should receive the flu vaccine (190, 19.1%). Pregnant women with flu vaccine knowledge score of ⩽5 (range 0–12) were significantly less likely to take the vaccine (OR 3.78, 95% CI 2.68–5.26, p < 0.001). There was a low uptake of the vaccine (178, 18.1%) and only 29 (3.0%) had previously been offered the flu vaccine by any doctor during their pregnancy. In addition, 255 (25.8%) were against taking the flu vaccine during pregnancy. Conclusion: The knowledge and uptake of the influenza vaccine among Saudi pregnant women are low. One quarter was against the vaccine during pregnancy. Very few believed the flu vaccine to be safe during pregnancy. Rarely, physicians advise their clients to take flu vaccine.